MAGIC3D FDTD EM-PIC code non-conformal geometry (cut cell) implementation - Woods, Andrew; Ludeking, L. (2015)
© 2014 IEEE. The MAGIC3D finite difference time domain electromagnetic particle-in-cell (FDTD EM-PIC) code has been upgraded to include non-conformal or 'cut' cells. The code solves Maxwell's equations in Cartesian coordinates using full and partial cells cut arbitrarily along flat surfaces. A field remapping treatment combines small volumes into neighbor cells to prevent undue Courant time step limitations. Models used for validation of results have included a circular waveguide and a coax both with ports and incoming 2GHz TE waves. Exiting microwave power is nearly identical for partial and full cells for well-zoned models, while some improvements are seen for coarse zones. A serpentine folded waveguide also showed nearly identical power to the step cell model.